2017
DOI: 10.4236/adr.2017.53014
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Improvising: The Be-Bop Language and the Dominant Seventh Chords

Abstract: The aim of this article lies fundamentally in illustrating the first part of a simple and intuitive method, finalized to "speaking" the Be-Bop language immediately, without possessing any jazz background whatsoever. The main peculiarity of the method consists in the fact that the attention of the improviser is always focused on Triads. We herein exclusively discuss the improvisation techniques regarding the dominant seventh chords. Starting from a specific extended "sentence", built around the Major Triad, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
11

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
0
6
0
11
Order By: Relevance
“…Nonetheless, all the sentences herein deduced, net of possible "enrichments" (Cataldo, 2017) and combinations with "public domain" patterns (Coker et al, 1982;Nelson, 2010), can be easily found by examining well-known solo transcriptions (Garland, 1999;Kelly, 2013;Parker, 1978;Powell, 1998Powell, , 2002.…”
Section: Brief Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, all the sentences herein deduced, net of possible "enrichments" (Cataldo, 2017) and combinations with "public domain" patterns (Coker et al, 1982;Nelson, 2010), can be easily found by examining well-known solo transcriptions (Garland, 1999;Kelly, 2013;Parker, 1978;Powell, 1998Powell, , 2002.…”
Section: Brief Conclusionmentioning
confidence: 99%
“…On this subject, exploiting the first part of the method (Cataldo, 2017), let's consider one of the "fundamental sentences" that can be played on F7. The sentence in question is shown in Figure 4, with the chordal notes (the ones that constitute the F Major Triad) depicted in red, and the minor seventh (with respect to F) depicted in green.…”
Section: The "Corresponding" Dominant Seventh Chordmentioning
confidence: 99%
See 1 more Smart Citation
“…As elsewhere underlined (Cataldo, 2017a(Cataldo, , 2017b, this method constitutes nothing but a simplified introduction to the Be-Bop language. Nonetheless, all the sentences herein deduced, net of possible "enrichments" (Cataldo, 2017a) and combinations with "public domain" patterns (Coker et al, 1982;Nelson, 2010), can be easily found by examining well-known solo transcriptions (Garland, 1999;Kelly, 2013;Parker, 1978;Powell, 1998Powell, , 2002.…”
Section: Brief Conclusionmentioning
confidence: 99%
“…The sentences so obtained can be easily cut, modified, by using new "words" (Wise, 1983) and extensions, and then combined. As elsewhere discussed (Cataldo, 2017a(Cataldo, , 2017b, the peculiarity of the method lies fundamentally in the fact that the attention of the improviser is focused on triads.…”
Section: Introductionmentioning
confidence: 99%